A Systematic Literature Review: Design and Control of Warehouse Order Picking in Development of E-commerce Transaction - Dida Diah Damayanti; Prafajar Suksessanno Muttaqin; Erlangga Bayu Setyawan; Nia Novitasari (International Journal of Innovation in Enterprise System, 2024)
Order picking is the process of retrieving items from storage to meet a specific customer order, whichis known to be the most labor-intensive and costly function among all the warehouse functions. Thisfunction is also important in that it has a critical impact on downstream customer service especiallyin facing the current covid-19 pandemic. This research aims to provide information, description andmore comprehensively identifies the design and control of warehouse order picking by usingempirical literature review. In this research, the stages are Identification of potential study, StudySelection based on criteria, quality assessment, data extraction, and data analysis. Based on theliterature review systematically compiled it is obtained 37 main articles that correspond to the purposeof research. From these 37 articles can be identified further research on design and control ofwarehouse order picking that provides increased transactions in e-commerce.